BURNOUT AS AN OCCUPATIONAL DISEASE AND CORPORATE OMISSION: ANALYSIS IN LIGHT OF ILO CONVENTION 190: ANÁLISE À LUZ DA CONVENÇÃO 190 DA OIT (ESMAT Magazine, 2025)
This article analyzes the employer's legal responsibility in relation toburnout syndrome, understood as an occupational disease linked to harmful organizationalpractices. The research is based on the premise that burnout results from a workenvironment characterized by abusive targets, exhausting workloads, and neglect ofworkers' mental health. Through an interdisciplinary approach and legal foundation, thestudy examines constitutional, infraconstitutional, and international provisions that imposeon employers the duty to prevent psychosocial risks. The article highlights the relevance ofILO Convention nº 190, which, although not yet ratified by Brazil, introduces broaddefinitions of violence and harassment in the workplace and reinforces mental healthprotection as a core dimension of decent work. It concludes that the employer’s omissionin adopting preventive measures against burnout constitutes a violation of the worker’sfundamental rights and gives rise to labor, civil, and social security liability. Furthermore,it argues that the principles of Convention 190, in harmony with the national legal system,may be used as an interpretative source for judicial decisions and public policies aimed atpromoting healthy work environments.
Keywords: Occupational Disease; Burnout; Convention n.190 ILO